RESPONS PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) PADA BERBAGAI DOSIS PUPUK KANDANG SAPI DAN PUPUK NPK - Mohamad Fadli; Syahrani Syahrani; Melinda Gracy Kristin (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2021)
The research aim to determine the effect of growth and yield the onion to the on dose of manure and NPK fertilizer. This research was conducted since March to June 2021, at Sumber Rejeki, Dusun Merangan, Desa Loh Sumber, Kecamatan Loa Kulu, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur. This study used a randomized complete block design (RCBD) factorial pattern with three replications. Treatment of cow manure consists of 3 level and Treatment of NPK fertilizer consists of 3 level, in order to obtain 9 units of research, namely : k0n0 (control), k0n1 (control + 25 g NPK), k0n2 (control + 50 g NPK), k1n0 (3 kg cow manure + control), k1n1 (3 kg cow manure + 25 g NPK), k1n2 (3 kg cow manure + 50 g NPK), k2n0 (6 kg cow manure + control), k2n1 (6 kg cow manure + 25 g NPK), k2n2 (6 kg cow manure + 50 g NPK). The results showed that the on treatment of cow manure had no significant effect on the average number of leaves aged 15, 30, 45 HST, number of tubers, tuber weight, and yield per hectare. The result highest in per hectare that is in treatment k2 (6 kg per plot) with an average 9,96 t ha-1 and lowest yield on k1 (3 kg per plot) with an average 9,07 t ha-1. The result of interaction between various cow manure and NPK fertilizer have no significant on all parameters. The highest average of per hectare is on treatment k2n1 with the result 10.4 t ha-1. The lowest average of per hectare is on treatment k1n2 with the result 7.7 t ha-1.